2012
DOI: 10.1063/1.4753940
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and structural properties of aqueous nonpolar solute mixtures

Abstract: The dielectric properties and molecular structure of water mixtures with different nonpolar solutes (methane and noble gases) are studied using molecular dynamics. The water-water, water-solute, and solute-solute interactions are calculated using the combination of a polarizable potential [J. Li, Z. Zhou, and R. J. Sadus, J. Chem. Phys. 127, 154509 (2007)] for water plus the Lennard-Jones potential. The effect of solute size and concentration on the solubility of the system, hydrogen bonding, dielectric consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The H-bond network is most extensive at ambient conditions (25•C and 1 atm) when water molecules can form up to four hydrogen bonds. As the temperature and pressure increase, the average number of H-bonds per water molecule decreases (Shvab and Sadus, 2012). a n u s c r i p t 8 A model that captures the correct physical features of the system of interest is imperative for the successful molecular simulation of water and aqueous solutions (Vega and Abascal, 2011;Yigzawe and Sadus, 2013a).…”
Section: Water and Hydrogen Bondingmentioning
confidence: 99%
See 3 more Smart Citations
“…The H-bond network is most extensive at ambient conditions (25•C and 1 atm) when water molecules can form up to four hydrogen bonds. As the temperature and pressure increase, the average number of H-bonds per water molecule decreases (Shvab and Sadus, 2012). a n u s c r i p t 8 A model that captures the correct physical features of the system of interest is imperative for the successful molecular simulation of water and aqueous solutions (Vega and Abascal, 2011;Yigzawe and Sadus, 2013a).…”
Section: Water and Hydrogen Bondingmentioning
confidence: 99%
“…Lie and Clementi (1986) argued that the MCY potential is too repulsive, which only allowed the computation of a small number of configurations used for fitting, and concluded that this compact configuration is the main reason for the prediction of high pressures. Among the good qualities of the MCY model are the correct representation of O-H and H-H RDFs (Shvab and Sadus, 2012). The model is important from a historical perspective, and it forms the basis for more advanced models that include bond flexibility (Lie and Clementi, 1986), three-body and polarization interaction terms (Niesar et al, 1990;Li et al, 2007).…”
Section: Mcy Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The study on the effect of dissolution of methane in NaCl aqueous solution, or seawater, is an issue of great interest, because dissolution of methane into seawater may affect the earth environment. Though many molecular dynamics (MD) study dealing with methane hydrate have been performed [2], most of them are on the stand point of nucleation, or in the supercritical condition in pure water. In this study, we perform MD simulation of methane and NaCl solution similar concentration to seawater.…”
Section: Introductionmentioning
confidence: 99%